Preliminary study of the rodent assemblages of Goda Buticha: New insights on Late Quaternary environmental and cultural changes in southeastern Ethiopia. (25th March 2018) - Stoetzel, Emmanuelle; Sime, Workalemahu Bekele; Pleurdeau, David; Asrat, Asfawossen; Assefa, Zelalem; Desclaux, Emmanuel; Denys, Christiane
Abstract: Given its proximity to the Strait of Bab el Mandeb and the Red Sea, the Horn of Africa is particularly important for understanding human and faunal migration events to and from Africa. Towards the end of the Pleistocene, the Middle/Later Stone Age (MSA/LSA) transition represents a critical step in human cultural evolution. However, in the Horn of Africa, the environmental conditions associated with this transition remain poorly understood. The Goda Buticha (Buticha cave) sequence, located in southeastern Ethiopia, and dated from ca. 63 ka cal BP to ca. 1 ka cal BP, provides a rare opportunity to examine the environmental contexts associated with major cultural sequences documented in the region during this time period. A preliminary analysis of the rich microvertebrate (and especially rodent) remains recovered from the levels dated between 43 and 4 ka BP identified fourteen different rodent genera, including two species that are locally extinct in southeastern Ethiopia today. While the taphonomic signature is similar throughout the sequence, indicating an in situ accumulation by an owl without major perturbation, the palaeoecological analysis showed environmental change through time, characterized by open-dry setting during the Late Pleistocene, shifting to wetter and more wooded conditions heading to the Holocene. These results are generally consistent with other diverse records which include the large mammals, speleothems and lake basins records, and allow a better understanding of the dynamics of environmental contexts associated with observed cultural change and continuity in eastern Africa from the Late Pleistocene to Late Holocene.